Local Drug-Induced Modulation of gp130 Receptor Signaling Delays Disease Progression in a Pig Model of Temporo-Mandibular Joint Osteoarthritis - Liu, Nancy Q.; Chen, Shuo; Geng, Dawei; Lei, Jie; Zhang, Jiankang; Li, Liangliang; Lin, Yucheng; Ouyang, Yuxin; Shkhyan, Ruzanna; Van Handel, Ben; Bian, Fangzhou; Mkaratigwa, Tadiwanashe; et al. (Frontiers in Dental Medicine, 2022)
Temporomandibular joint disorders (TMJs) are a multifaceted group of chronic disorders characterized by stiffness in the jaw, limited jaw mobility and pain when opening or closing the mouth. TMJs are relatively common, with incidence rates in the range of 5-12%, with nearly twice as many women as men being affected. One of the primary causes of TMJs is a degenerative disease of joints, such as osteoarthritis (OA), characterized by progressive loss of cartilage which causes stiffness, swelling and pain. Currently, there are no disease-modifying agents on the market for OA. We have recently discovered a small molecule, R805 acting as a modulator of glycoprotein 130 (gp130) receptor for IL-6 family of cytokines. R805 enables regenerative outputs of endogenous joint stem and progenitor cells through immunomodulation in the joint microenvironment by reducing the levels of destructive cytokines and supporting chondrocyte survival and anabolism. Extensive testing has shown R805 to be safe at doses far above the therapeutic level. Here, we have conducted a pivotal efficacy study in our newly-established pig model of TMJ post-traumatic OA. IA injection of R805 has shown a highly significant reduction of articular cartilage degeneration, reduced synovitis and degenerative changes in subchondral bone in the mandibular condyle compared to the vehicle-treated group. These data will support additional pre-clinical development of R805 as a first-in-class injectable therapeutic for TMJ osteoarthritis.